Dynamic consensus method design for a multi-agent system - Zhao, Jingyuan (Nanyang Technological University, 2024)
In the realm of multi-agent systems (MAS), where autonomous entities collaborate towards common goals, achieving consensus among agents is pivotal. Consensus, in essence, embodies the collective agreement or convergence states among multiple entities in the system. The dynamic consensus problem within MAS pertains to situations where the agents' interactions and the input signals evolve over time, presenting a challenge in maintaining agreement amidst changing conditions. However, most studies focus on the multi-agent systems with static graph topology. Only a few works discussed the open multi-agent systems. In this dissertation, a dynamic consensus algorithm for open multi-agent systems will be given. Besides, this dissertation will also discuss the convergence of the algorithm from the perspective of graph splitting and merging.